2017
DOI: 10.4269/ajtmh.16-0586
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Gene Confirms the Specific Status of Triatoma pintodiasi Jurberg, Cunha, and Rocha, 2013 (Hemiptera, Triatominae), an Endemic Species in Brazil

Abstract: Abstract. Chagas disease is most frequently transmitted to humans through contact with feces of insects from the Triatominae subfamily. In Brazil, there are 65 species of triatomines distributed throughout the country's 27 states. Among the species in the state of Rio Grande do Sul, Triatoma rubrovaria, Triatoma oliveirai, Triatoma pintodiasi, Triatoma klugi, Triatoma carcavalloi, and Triatoma circummaculata (with the addition Triatoma limai, which is endemic to Argentina) form the T. rubrovaria subcomplex. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…17 On the other hand, the different mitochondrial genes analyzed demonstrated high intraspecific variation between the genetic distances of T. vitticeps from different states ranging from 2.3% to 7.5% (Tables 2-4). Pereira et al 18 consider that 19 Based on this, different authors evaluated the specific status of triatomines by means of genetic distance using mitochondrial genes: Alevi et al 20 through the 16S gene corroborates the specific status of Triatoma pintodiasi Jurberg et al (2013); Alevi et al 21 through the 16S gene also have proposed the synonimization between Nesotriatoma bruneri Usinger (1944) and Nesotriatoma flavida (Neiva, 1911); Ceretti-Junior et al 14 based on the 16S gene reported low intraspecific variation between genetic distances of triatomines (0-0.6%), except for relationships between Triatoma brasiliensis Neiva (1911) specimens (1.3%) and Triatoma sordida (St ål, 1859) specimens (1%) from different geographic populations (specimens that possibly suffered cryptic speciation) 22,23 ; Panzera et al 23 using the COI gene observed a genetic distance of 5.3% between T. sordida from Brazil and from Argentina and suggest that T. sordida from Argentina is possibly a new cryptic species of T. sordida; Abad-Franch et al 24 used the genetic distance of cyt b (8.7%) between Rhodnius robustus Larrousse (1927) and Rhodnius barretti to characterize that R. barretti represents a distinct entity within the "robustus lineage"; and Rua et al 25 suggested that populations of Triatoma sanguisuga (Leconte, 1855) are divided into two subspecies because they have genetic distances close to five for cyt b.…”
mentioning
confidence: 99%
“…17 On the other hand, the different mitochondrial genes analyzed demonstrated high intraspecific variation between the genetic distances of T. vitticeps from different states ranging from 2.3% to 7.5% (Tables 2-4). Pereira et al 18 consider that 19 Based on this, different authors evaluated the specific status of triatomines by means of genetic distance using mitochondrial genes: Alevi et al 20 through the 16S gene corroborates the specific status of Triatoma pintodiasi Jurberg et al (2013); Alevi et al 21 through the 16S gene also have proposed the synonimization between Nesotriatoma bruneri Usinger (1944) and Nesotriatoma flavida (Neiva, 1911); Ceretti-Junior et al 14 based on the 16S gene reported low intraspecific variation between genetic distances of triatomines (0-0.6%), except for relationships between Triatoma brasiliensis Neiva (1911) specimens (1.3%) and Triatoma sordida (St ål, 1859) specimens (1%) from different geographic populations (specimens that possibly suffered cryptic speciation) 22,23 ; Panzera et al 23 using the COI gene observed a genetic distance of 5.3% between T. sordida from Brazil and from Argentina and suggest that T. sordida from Argentina is possibly a new cryptic species of T. sordida; Abad-Franch et al 24 used the genetic distance of cyt b (8.7%) between Rhodnius robustus Larrousse (1927) and Rhodnius barretti to characterize that R. barretti represents a distinct entity within the "robustus lineage"; and Rua et al 25 suggested that populations of Triatoma sanguisuga (Leconte, 1855) are divided into two subspecies because they have genetic distances close to five for cyt b.…”
mentioning
confidence: 99%